AN ANALYTICAL STUDY ON WOMEN EMPOWERMENT THROUGH SOCIAL MEDIA - V. SINJITHA * and R. JANSI RANI, (The Journal of Research ANGRAU, 2022)
The study conducted during 2021–22 aimed to evaluate the socio-demographic profile ofeducated homemakers between the age group of 34 and 54 to recognize the influence of socialmedia and to realize the impact of social media on women home makers. The adoptive structurationtheory was used to enhance homemakers’ capacities by improving their technology acceptanceamong people who are unable to work independently and compelled to rely on their spouses forfinancial assistance. The results of the study showed that 90 percent of the homemakers werefamiliar with online commerce and social media utilization, which isn’t always feasible for earningadditional money by homemakers because they’re overburdened with domestic responsibilities.However, the respondents could gain valuable insights into technology adoption.